Interpersonal Relationships, Motivation, Engagement, and Achievement: Yields for Theory, Current Issues, and Educational Practice - Martin, Andrew J.; Dowson, Martin (Review of Educational Research, 2009)
In this review, we scope the role of interpersonal relationships in students’ academic motivation, engagement, and achievement. We argue that achievement motivation theory, current issues, and educational practice can be conceptualized in relational terms. Influential theorizing, including attribution theory, expectancy-value theory, goal theory, self-determination theory, self-efficacy theory, and self-worth motivation theory, is reviewed in the context of the role of significant others in young people’s academic lives. Implications for educational practice are examined in the light of these theoretical perspectives and their component constructs and mechanisms. A trilevel framework is proposed as an integrative and relationally based response to enhance students’ motivation, engagement, and achievement. This framework encompasses student-level action (universal programs and intervention, targeted programs for at-risk populations, extracurricular activity, cooperative learning, and mentoring), teacher- and classroom-level action (connective instruction, professional development, teacher retention, teacher training, and classroom composition), and school-level action (school as community and effective leadership).